Gene therapy approaches to enhancing plasticity and regeneration after spinal cord injury - Franz, Steffen; Weidner, Norbert; Blesch, Armin (Experimental neurology, 2012)
During the past decades, new insights into mechanisms that limit plasticity and functional recovery after spinal cord injury have spurred the development of novel approaches to enhance axonal regeneration and rearrangement of spared circuitry. Gene therapy may provide one means to address mechanisms that underlie the insufficient regenerative response of injured neurons and can also be used to identify factors important for axonal growth. Several genetic approaches aimed to modulate the environment of injured axons, for example by localized expression of growth factors, to enhance axonal sprouting and regeneration and to guide regenerating axons towards their target have been described. In addition, genetic modification of injured neurons via intraparenchymal injection, or via retrograde transport of viral vectors has been used to manipulate the intrinsic growth capacity of injured neurons. In this review we will summarize some of the progress and limitations of cell transplantation and gene therapy to enhance axonal bridging and regeneration across a lesion site, and to maximize the function, collateral sprouting and connectivity of spared axonal systems.